Towards optimized lubrication by micro texturing of tool surfaces - Neudecker, Thomas; Popp, Uwe; Engel, Ulf; Geiger, Manfred (Advanced Technology of Plasticity 1999, Proc. of the 6th Int. Conf. on Technology of Plasticity, Vol. 1, 1999)
None
LFT Import::2019-08-05 (1998)